Secure Quantum Communication With Multi-Users in Quantum Networks - As'Ad Mahmoud As'Ad Alnaser; Hazem Moh'D Said Hatamleh; Nawaf Abdualziz Almolhis; Salahaldeen Duraibi; Yahya Alqahtani (IEEE Open Journal of the Communications Society)
Quantum Key Distribution (QKD) and encryption protocols are central to secure user-to-user communication in quantum networks. However, the detection of eavesdropping, security vulnerabilities, and performance degradation at high traffic levels are some of the challenges faced by inefficient multi-user communication. Current approaches do not adequately overcome these challenges. This paper suggests a holistic framework that integrates QKD, classical-quantum multiple access techniques, and advanced security protocols for overcoming these issues. This framework uses the QKD-SCM for communication security across several nodes and makes use of classical-quantum multiple accesses for greater speed and scalability in communication. Security is then further optimized with the MUQQ-ESTMP GHZ based on Multi-User Quantum Protocol, (MUQPQ), where it optimizes queries across several users. Lattice-based cryptography is deployed to protect against quantum computing attacks, and for detecting eavesdropper attacks, the Reverse Reconciliation Algorithm for binary-input additive white Gaussian noise channel (RRA-BIAWGNC) is used. Furthermore, QPQB has been integrated as a searchable symmetric encryption protocol to safeguard the data in cloud storage. The performance of the system has been analyzed with metrics like detection accuracy of eavesdrop attack (97%), communication complexity (95%), effective key rate (590 b/s), communication efficiency (96%), and computational overhead (98%). Simulation has been carried out using ns-3.30.1 and Python. Simulation results indicate a considerable reduction in communication complexity up to 40% and enhanced detection accuracy that surpassed the existing stateof- the-art benchmarks. Through the integration of multiple advanced techniques for security, this research contributes to the development of scalable and quantum communication networks with security.